Effect of chewing gum on thirst: an integrative review - Aline Korki Arrabal Garcia; Lígia Fahl Fonseca; Rejane Kiyomi Furuya; Patrícia Dias Rabelo; Edilaine Giovanini Rossetto (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To identify and analyze the evidence on the effect of chewing gum on thirst in adults. Method: Integrative review, guided by the question: "What is the scientific evidence about the effects of chewing gum on adult's thirst?" LILACS, PubMed, Scopus and Web of Science were the databases consulted. Results: Of a total of 2,414 articles found, 12 papers were selected whose publications varied between 1991 and 2016. The use of chewing gum resulted in increased salivary volume (five studies), xerostomia relief (seven studies), and thirst reduction (four studies). It was not possible to establish the number of chewing gums per day, being frequent the recommendation to use as desired. There was a predominance of studies with patients under dialysis and with cancer. Conclusion: Chewing gum is an effective strategy to reduce thirst discomfort in adults.